Long-Term Prognosis of Patients with Esophageal Atresia and/or Tracheoesophageal Fistula - Bakal, Unal; Ersoz, Fikret; Eker, Irem; Sarac, Mehmet; Aydin, Mustafa; Kazez, Ahmet (Springer India, 2016)
Objective To investigate long-term prognosis of infants with esophageal atresia (EA) and/or tracheoesophageal fistula (TEF). Methods The data of patients with EA were investigated from their medical files. For the neurodevelopmental evaluation, they were requested to come for a return visit to authors' polyclinic. Intellectual development was assessed by Ankara Developmental Screening Inventory (ADSI) (for 0-6 age) and Wechsler Intelligence Scale for Children-Revised (WISC-R) (for 6-16 age). Results Of the 57 patients, 50 had EA+ distal TEF (87.7 %), six had isolated EA (10.5 %) and one had isolated TEF (1.8 %). Of the total patients, 18 cases (31 %) died and remaining 39 cases (69 %) survived. In the surviving cases, the most common long-term complication was dysphagia (n = 37, 94.8 %). Intellectual levels of the 24 patients assessed by ADSI were normal and of the remaining 15 cases evaluated by WISC-R ranged between 95 and 110 points. Conclusions The long-term complications and hospital visits are common in surviving cases of EA; however, they have normal cognitive functions and physical developmental characteristics.
Keywords: Esophageal atresia; Tracheoesophageal fistula; Prognosis; Cognitive function; Physical development; Growth retardation; Intelligence quotient